# math

posted by .

using method of partial fractions to decompose this 1/(x-3)(x+3)

is 1/6(x-3)-1/6(x+3) correct or have i gone wrong somewhere

• math -

I get

1/(x-3)(x+3) = A/(x-3) + B/(x+3)

1 = (x+3)A + (x-3)B

1 = x(A+B) + 3A -3B

-> A + B = 0 -> A = -B

-> 3A - 3B = 1 -> A = 1/6; B = -1/6

= (1/6)(x-3) - (1/6)/(x+3)

• math -

thanks so it is the same thank god for that

## Similar Questions

1. ### Calc easy

Having trouble getting the correct solution. The integral of “x squared” in the numerator and “x squared plus x minus 6” in the denominator. S X2 / (X2 + x – 6) dx Thanks! That's a messy one. According to my table of integrals. …
2. ### CALC 2 - Partial Functions!!

How do I solve Integral of 7/(16-x^2) I know I must break down (16-x^2) into (x+4)(-x+4), but after I do that what is next?
3. ### Calculus - Partial Fractions

What is the integral of 7e^(7t) Divided By e^14t+13e^7t+36 Using partial fractions
4. ### Algebra

Is this right? Decompose into partial fractions. (2x^2-24x+35)/(x^2+2x-7)(x-2)= (Ax+B)/(x^2+2x-7)+C/(x-2) =Ax^2+Bx-2Ax-2B+Cx^2+2xC-7C =(A+C)x^2+Bx+2(Ax+Cx-B)-7C A+C=2 2Ax+Bx+2Cx=24 -2B-7C=35 A=2-C B=(35-7C)/(-2)
5. ### Pre-Algebra [repost for Reiny]

In my last post for #1, I asked my teacher and she said that it's actually k=30 . Could you have gone wrong somewhere?
6. ### Binomial

Help me on this one :( Express y= (7-3x-x^2)/[((1-x)^2)(2+x)] in partial fractions. Hence, prove that if x^3 and higher powers of x may be neglected, then y=(1/8)(28+30x+41x^2) I did the first part of expressing it in partial fractions. …
7. ### Calculus

Find the integral of x/ (x^4+x^2+1) from 2 to 3. I was going to integrate using the method for partial fractions but I can't factor x^4+x^2+1.
8. ### calculus

Decompose 58-x/x^2-6x-16 into partial fractions.
9. ### Math- Partial Fractions

Decompose the following into partial fractions after factoring the denominator as much as possible. Please show some work so I can understand how you did it. 1)x^2/((x-1)(x^2+5x+4)) 2)(3x^3-5x^2+12x+4)/(x^4-16) 3)1/(x^2 (x+1)^2 ) 4)(x+1)/((x^2+1) …
10. ### Math Help

Directions: Decide whether the statements are true or false by using partial fraction decomposition. If the statement is false, show the correct way to decompose the partial fraction. 3/x^2+x-2=-1/x+2+1/x-1

More Similar Questions

Post a New Question